Hydrogeology in Algeria - Kessasra, Farès; Mezerreg, Nour-Houda (Acque Sotterranee - Italian Journal of Groundwater, 2023)
As climate change is growing, water security becomes an urgent challenge in the Middle East and North Africa (MENA), the most water scarce region in the world (World Bank, 2018; UN Water, 2020). Algeria is one of these countries under large stresses (Kwasi & Cilliers, 2020). The water stress index is poor with a water availability ratio of 411 m3/cap/year. Forecasts estimate a value of 300 m3/cap/year in 2050 (Falkenmark et al., 1989; Kherbache, 2020). Although, the natural factors (climate change) affect the access to water and lead either to severe water shortages and regional disparities, the water deficit is mainly due to a lack of sustainable groundwater management associated to poor knowledge of the resource (PNE,2010; Kherbache, 2020) [...].